The Relationship Between Food Acceptance And Usual Food Leftovers In Inpatients At Rsud dr. R. Koesma Tuban - Qodriatika, Norma Amalia; Nafies, Dian Ayu Ainun (Universitas Negeri Medan, 2024)
The provision of food in hospitals is said to be successful if food waste from inpatients in the hospital reaches <20%. According to the survey results, the percentage of food waste at RSUD dr. R. Koesma Tuban still has not reached the minimum service standard. The aim of this research is to determine the relationship between the acceptability of food taste and regular food waste in inpatients. Correlational analytical research method with a cross sectional approach. The sample for this research consisted of 133 respondents, determined using incidental sampling techniques. Research analysis uses the contingency coefficient statistical test. The results of the research show that most of the food's acceptability is in the delicious category with an average of 81%, while the remaining food is in the large category (>20%) with an average of 22%. The conclusion from this research is that there is a lot of food waste at RSUD dr. R Koesma Tuban is not influenced by the taste of the food served, but there are other factors that influence the amount of leftover food in patients, namely a decrease in appetite in patients. So there was no significant relationship found between the acceptability of food taste and food waste.